2018
DOI: 10.5507/tk.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

Does active commuting help Czech adolescents meet health recommendations for physical activity?

Abstract: Východiska: Pohybová aktivita (PA) je velmi důležitým faktorem ovlivňujícím lidské zdraví. Aktivní docházka/ dojížďka (AD) do školy může napomoci zvýšit celkový počet kroků za den a tím snáze plnit zdravotní doporučení pro PA. Pro zlepšení propagace a zvýšení využití AD je důležité co nejlépe identifikovat faktory ovlivňující volbu této formy transportu. Cíle: Cílem této studie bylo zjistit, zda AD do školy pomáhá žákům v České republice plnit zdravotní doporučení pro PA. Dílčím cílem bylo zjistit, jak volbu f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, the findings of Vorlíček et al [17,18] on a sample of Czech adolescents indicate that there might be room for targeted intervention based on the social norms approach to increase the PA of adolescents or at least strengthen their actual positive behaviour.…”
Section: If Widespread Participation Indicates Social Acceptability I...mentioning
confidence: 99%
“…In addition, the findings of Vorlíček et al [17,18] on a sample of Czech adolescents indicate that there might be room for targeted intervention based on the social norms approach to increase the PA of adolescents or at least strengthen their actual positive behaviour.…”
Section: If Widespread Participation Indicates Social Acceptability I...mentioning
confidence: 99%
“…One of the ways to contribute to obtaining this amount of PA is through active commuting (AC) to/from school [12][13][14][15][16][17]. Previous findings have confirmed that AC to school contributed to the successful achievement of health recommendations for PA in Czech adolescents [18].…”
Section: Introductionmentioning
confidence: 99%